Fluorescence-guided resection of glioma using «photoditazin» - A. Yu. Rynda; D. M. Rostovtsev; V. E. Olyushin; Yu. M. Zabrodskaya (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The aim of this research was to improve results of gloss total resections of glial tumors of the brain. MATERIAL AND METHODS. Fluorescence-guided resection was performed in 31 patients with glial tumors of different degree of malignancy. «Photoditazin» was applied during operation. The authors assessed the efficacy, sensitivity and specificity of the method and degree of radical nature of resection in relation to surgery of gliomas. RESULTS. Sensitivity of the method numbered 68,3 % and specificity was 60,1 % in cases of gliomas of grade I-II. It was 85,4 % and 76,2 %, respectively in cases of gliomas of grade III-IV. The degree of achievement of gloss total resection (GTR) was 79,3 % (gliomas of grade III-IV) and 95,6 % (gliomas of grade III-IV). CONCLUSIONS. Intraoperative fluorescent diagnostics using «Photoditazin» was highly effective, sensitive and very specific method in surgery of glial tumors of different degree of malignancy. The method allowed doctors to develop the radical nature of surgery in cases of glial tumors removal.